The May 8 uprising and its repercussions and the position of Saudi Arabia towards it (Journal of the College of Basic Education, 2019)
It is clear to us from the above the most important reasons and motives that led to the outbreak of the uprising of May 1958, as well as the course of its results and the position of the Kingdom of Saudi Arabia of those events as its position fluctuated but most of it was inclined to neutrality and the research section to two topics dealt with the first topic of the uprising of May 1958 and the position of the Kingdom of Arabia Saudi Arabia, including the second topic dealt with the American descent in Lebanon and the position of the Kingdom of Saudi Arabia.